Pembangunan dan penilaian perisian prototaip MS~GraviS berasaskan kemahiran berfikir secara kritis dalam mekanik - Ahamad, Masrah (2006)
The purpose of this research is to develop prototype software, MS~GraviS, which is used to enhance undergraduate student’s critical thinking skills of Mechanics (Statics) in Centroids and Centre of Gravity topics by using WGCTA (Watson-Glaser Critical Thinking Appraisal). MS~GraviS consisted of five critical thinking skills namely Inference, Recognition of Assumptions, Deduction, Interpretation and Evaluation of Arguments. The contents in Centroids and Centre of Gravity was structured in FIKIRIS Engine (Critical Thinking Engine) environment to produce a new set of WGCTA-MS-GraviS (Watson-Glaser Critical Thinking Appraisal- Mechanics (Statics)- Centroids and Centre of Gravity). This research was done referred to research design and developed to enhance student’s understanding of Centroids and Centre of Gravity concepts based on constructivism and critical thinking theories. The effectiveness of MS~GraviS was evaluated by analyzing student’s concepts and their critical thinking skills. The Rapid Prototyping Model was emphasized during the entire development of MS~GraviS. Macromedia Flash was used to develop MS~GraviS. The software was evaluated using samples of ten students from Faculty of Education (FP), Faculty of Science (FS) and Faculty of Chemical Engineering and Natural Resources (FKKSA), UTM who had studied Mechanics (Statics) for the first time. The analysis was conducted in three part namely before the usage, while using the software and after using the software. The instruments used in gathering the research data encompassed a range of tests, digital camcorder, observations, interviews and worksheets. The analysis revealed that MS~GraviS is capable of increasing student’s understanding in learning Centroids and Centre of Gravity concepts, as well as enhancing the critical thinking skills in Centroids and Centre of Gravity topics. Generally, students show an improvement of performance in nearly all Centroids and Centre of Gravity concepts and critical thinking skills that had been surveyed after the application of MS~GraviS.